Possibilities of a software-based hybrid single photon emission computed tomography/ magnetic resonance imaging in the diagnosis of complicated diabetic foot syndrome - V. D. Zavadovskaya; M. A. Zorkal’tsev; V. D. Udodov; M. A. Zamyshevskaya; O. Yu. Kilina; A. P. Kurazhov; K. M. Popov (Вестник рентгенологии и радиологии)
Objective: to give the results of a software-based hybrid single photon emission computed tomography/magnetic resonance imaging (SPECT/MRI) in detecting osteomyelitis (OM) in patients with diabetic foot syndrome (DFS).Material and methods. Seventy-six patients (35 men and 41 women) (mean age, 59.4±7.1 years) with type 1 and 2 diabetes mellitus and suspected OM were examined. The investigation enrolled patients with neuropathic (n=25), ischemic (n=13), and mixed (n=38) DFS. All the patients underwent 99mTc-HMPAO/ 99mTc-technefit labeled leukocyte scintigraphy; magnetic resonance imaging was performed in 30 patients. The results were combined using RView 9.06 software (Colin Studholme).Results. Labeled leukocyte SPECT to diagnose OM yielded 25 true positive (TP), 38 true negative (TN), 12 false positive (FP), and 1 false negative (FN) results. The accuracy of the technique was 82.9%. The FP results were due to the low resolution of the technique and to the small sizes of the object under study. One FN result was detected in a patient with ischemic DFS because of reduced blood flow. MRI to identify OM in patients with DFS  provided 20 TP, 16 TN,4 FP, and 2 FN results. Its diagnostic accuracy was 85.7%. The relative low specificity of MRI was associated with the presence of FP results due to the complexity of differential diagnosis of bone marrow edema and inflammatory infiltration. Assessing 42 hybrid SPECT/MR-images revealed 21 TP, 17 TN, 3 FP, and 1 FN results. The diagnostic accuracy was equal to 95.9%.Conclusion. Thus, comparing MRI (90.9% sensitivity and 80.0% specificity), labeled leukocyte scintigraphy (96.2% sensitivity and 76.0% specificity), and hybrid SPECT/MRI (95.5% sensitivity and 85.0% specificity) showed the high diagnostic efficiency of the latter.